Muslim perception towards imported halal food in Kelantan - Nur Asma Natasha Che Ibrahim; Nur Asyira Ismail; Nur Atikah Normahazam; Nur Azwani Mohamad Akhir (2023)
This thesis describes the perception of Muslim customers of imported Halal food. This study aims to investigate respondents who buy imported Halal food by examining the Halal logo, ingredients in the food, and the packaging of the food. The study design used in this study is a qualitative method. Next, this research aims to identify whether or not respondents research halal logos, ingredients, and even packaging. It consists of students from the University of Malaysia Kelantan, and the population of Kelantan. Nonprobability sampling was chosen for data collection in this study. We randomly interviewed students from the University of Malaysia Kelantan, as well as the population of Kelantan. The location of the sample is all the states of Kelantan. In addition, the population in this research is aimed at Muslim respondents who buy Halal food. Our respondents focused mainly on Muslim customers who buy imported Halal food. Therefore, this study also uses the Theory of Planned Behavior (TPB). Finally, this study used 5 respondents because the answers received by the researcher were saturated answers.